2017
DOI: 10.1111/joa.12616
|View full text |Cite
|
Sign up to set email alerts
|

Barn owls maximize head rotations by a combination of yawing and rolling in functionally diverse regions of the neck

Abstract: Owls are known for their outstanding neck mobility: these birds can rotate their heads more than 270°. The anatomical basis of this extraordinary neck rotation ability is not well understood. We used X-ray fluoroscopy of living owls as well as forced neck rotations in dead specimens and computer tomographic (CT) reconstructions to study how the individual cervical joints contribute to head rotation in barn owls (Tyto furcata pratincola). The X-ray data showed the natural posture of the neck, and the reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(73 citation statements)
references
References 23 publications
5
68
0
Order By: Relevance
“…In conclusion, our results are consistent with those of previous studies on the regionalization of the neck in birds (e.g., Virchow 1910;Boas 1929;Zweers et al 1987;van der Leeuw et al 2001;Tambussi et al 2012;Cobley et al 2013;Krings et al 2017;Kambic et al 2017). However, they indicate that the pattern of modularity is more complex than expected, including subdivisions of the traditional functional regions and module redundancy.…”
Section: The Three Functional Regions Hypothesissupporting
confidence: 93%
See 2 more Smart Citations
“…In conclusion, our results are consistent with those of previous studies on the regionalization of the neck in birds (e.g., Virchow 1910;Boas 1929;Zweers et al 1987;van der Leeuw et al 2001;Tambussi et al 2012;Cobley et al 2013;Krings et al 2017;Kambic et al 2017). However, they indicate that the pattern of modularity is more complex than expected, including subdivisions of the traditional functional regions and module redundancy.…”
Section: The Three Functional Regions Hypothesissupporting
confidence: 93%
“…These subdivisions consist only of redundant modules and therefore share similar (even if not identical) postural properties but present varied shapes. This finding is in line with those of Krings et al (2014Krings et al ( , 2017, who identified three to seven modules along the neck of owls based on morphological and functional studies.…”
Section: The Three Functional Regions Hypothesissupporting
confidence: 91%
See 1 more Smart Citation
“…To the extent that diminished range of motion limits load variability, safe development of more pneumatic bones could be brought about by serial decreases in flexibility in the caudal cervical vertebrae. Range of motion, at least in some axes, has been shown to decrease toward the base of the neck in some birds (Van der Leeuw et al, 2001; Dzemski & Christian, 2007; Cobley et al, 2013; Krings et al, 2017), though patterns of mobility are complex (Kambic et al, 2017). Caudal cervical vertebrae also likely benefit from the stabilizing and load‐sharing effects of relatively large intervertebral ligaments and the envelopment of the base of the neck by large masses of muscle (Dzemski & Christian, 2007; Cobley et al, 2013), perhaps further enabling increased pneumaticity in these elements.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have quantified lateroflexion in addition to, and independently of, dorsoventral flexion [ 26 , 33 ]. Only three studies have attempted to reconstruct bird neck movements in three dimensions (specifically in owls [ 35 , 39 , 40 ]), with the potential to quantify all three rotational degrees of freedom simultaneously, including axial rotation. Such data are critical for understanding joint function, as musculoskeletal movements incorporate motion around multiple degrees of freedom simultaneously (e.g.…”
Section: Introductionmentioning
confidence: 99%